On the popularization of digital close-range photogrammetry: a handbook for new users. - Χατζηφώτη, Όλγα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2016)
This handbook describes the current “snapshot” of the evolution process of Photogrammetry, a centuries-old and up to now expert-exclusive discipline. Photogrammetry has traditionally been a “tool of the trade” in the arsenal of the surveyor-engineer, serving the need for accurate spatial/geometrical documentation. Photogrammetry in the past has been a complicated and labour intensive process, which was available only to a small circle of experts and which had a specific scope of applications, with a heavy focus on cartography. The aforementioned «expansion» has been triggered by the advent of Digitization, in specific, by the digital sensors and the automation of the calculations & techniques involved in the photogrammetric process. The constant development of computer algorithms, alongside the improvement of the necessary hardware, has greatly amplified the efficiency and affordability of digital photogrammetry. Nowadays, it can potentially offer its benefits to a much wider audience, including experts from different disciplines or even non-expert users. For this process of “dissemination”, the soft- & hardware availability does not present itself so much as a problem, as “public awareness” & practical, technological knowhow do. At this evolutionary point, there is a great need for widespread information on the potential of digital photogrammetry and more importantly, for theoretical & practical training of the new user groups. > This effort is a (very) small step in this direction.